2003
DOI: 10.1046/j.1523-1747.2003.12011.x
|View full text |Cite
|
Sign up to set email alerts
|

Helium–Neon Laser Irradiation Stimulates Migration and Proliferation in Melanocytes and Induces Repigmentation in Segmental-Type Vitiligo

Abstract: Low-energy helium-neon lasers (632.8 nm) have been employed in a variety of clinical treatments including vitiligo management. Light-mediated reaction to low-energy laser irradiation is referred to as biostimulation rather than a thermal effect. This study sought to determine the theoretical basis and clinical evidence for the effectiveness of helium-neon lasers in treating vitiligo. Cultured keratinocytes and fibroblasts were irradiated with 0.5-1.5 J per cm2 helium-neon laser radiation. The effects of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 57 publications
(54 reference statements)
2
129
0
8
Order By: Relevance
“…LLLT can also induce collagen synthesis and growth factor secretion. Furthermore, there is also a downregulation of the production of pro-inflammatory cytokines and cell apoptosis by LLLT [14][15][16][17][18][19][20].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelmentioning
confidence: 99%
“…LLLT can also induce collagen synthesis and growth factor secretion. Furthermore, there is also a downregulation of the production of pro-inflammatory cytokines and cell apoptosis by LLLT [14][15][16][17][18][19][20].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelmentioning
confidence: 99%
“…The favourable effects of polarized light rays were discovered during studies on laser light rays, and in 1981 a group of physicists from Hungary proved that polarized light has a stimulating effect on the natural defence and repair functions of organisms and cells (Kertesz et al, 1982;Fenyo, 1984;Kubasova et al, 1988). These cells include endothelial cells (Moore et al, 2005), keratinocytes (Yu et al, 2003), macrophages (Fujimaki et al, 2003), and several classes of leukocytes such as neutrophils (Young et al, 1989). Earlier research on bacteria showed a significant difference (P < 0.05) in the number of Bacillus subtilis after treatment with non-coherent polarized light, darkness or visible light .…”
Section: Resultsmentioning
confidence: 99%
“…In vitro study on cultured keratinocytes and melanocytes conducted by Yu and colleagues showed that helium-neon laser could stimulate proliferation and migration of melanocytes. Their study on the efficacy of this kind of laser on patients with segmental vitiligo revealed positive responses (> 50% repigmentation in 60% of patients with segmental vitiligo) (Yu et al, 2003).…”
Section: Phototherapymentioning
confidence: 99%